Penentuan Urutan Prioritas Pemeliharaan Bangunan SMA Bina Generasi Bangsa Meulaboh-Aceh Barat - Edi Mawardi; Rahmat Djamaluddin (Universitas Teuku Umar, 2018)
Building school as a means of education for the smooth process of teaching and learning. With the maintenance of poor buildings cause the various functions of building facilities decreases and affects the quality and comfort of building users. If the damage to building components is left then slowly the service life of the building will decrease. View function of High School building Bina Generasi Bangsa Meulaboh, then it should be this building gets good maintenance for the reliability and feasibility of buildings in the architecture, structure, and utilities remain awake and function optimally. The purpose of this research is to know the priority of building maintenance. The method of analysis used statistical methods and Analytical Hierarcy Process (AHP). The result of analysis of priority sequence of maintenance of asitektur element can be first priority that is roof covering, while second priority on structural element that is column, beam and floor plate. While the utility element gets the twelfth priority and so on. Keywords : School Building, Order of Maintenance, Analytical Hierarcy Process (AHP).